Dimensions of Subject Knowledge and Their Perceived Significance for Teachers in Romania - Carmen Gabriela Lăzăreanu; Alexandra Apetrăcheoae (MDPI AG, 2023)
Knowing the content of the matter one is teaching seems to be an implicit requirement. There are, however, some nuances between learning, understanding, needing to reproduce information exactly or adapt it. In this quantitative study, we tried to assess teachers' perceptions on this issue based on their professional experience. Thus, we tried to highlight which aspects of knowledge are important and valued in the direct experience with pupils and how these are reflected in the evaluations and competitions organised institutionally for teacher tenure. The sample consists of 1154 Romanian teachers in pre-university education, with national representativeness and a proportional distribution per country region. The main motivation of this study is the need to support Romanian educational policies to find appropriate evaluation formulas for candidates in accordance with the concrete requirements of the profession, as shown in the direct work with students. This approach could encourage candidates to better prepare both for the qualification exam and to develop the skills needed to engage with pupils to improve classroom work in a more realistic way, adjusted to concrete conditions. The results of the research invite us to consider the importance of evaluating teachers in accordance with classroom needs.